2022
DOI: 10.3389/fimmu.2022.893617
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Gut Microbial-Derived Exosomes in Metabolic-Associated Fatty Liver Disease: Implications for Treatment

Abstract: The prevalence and incidence of metabolic-associated fatty liver disease (MAFLD), a clinically heterogeneous disease whose primary clinical therapies include dietary control and exercise therapy, is increasing worldwide and constitutes a significant medical burden. Gut microbes influence the physiopathological processes of the liver through different mechanisms based on the gut-liver axis. Exosomes are essential carriers of intercellular communication. Most previous studies have focused on adipocyte- and hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 90 publications
(100 reference statements)
2
14
0
Order By: Relevance
“…Based on our findings, it is important to mention that the liver has tissue specific configuration of enzymes, which can be targeted using proteomics studies since significant differences in enzymes in chronic liver diseases can be profiled 48,49 . Thus, the so called one‐carbon metabolism comprises a series of metabolic pathways, providing 1C units (methyl groups) and is crucial for biological methylation reactions 50 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on our findings, it is important to mention that the liver has tissue specific configuration of enzymes, which can be targeted using proteomics studies since significant differences in enzymes in chronic liver diseases can be profiled 48,49 . Thus, the so called one‐carbon metabolism comprises a series of metabolic pathways, providing 1C units (methyl groups) and is crucial for biological methylation reactions 50 .…”
Section: Discussionmentioning
confidence: 87%
“…47 Based on our findings, it is important to mention that the liver has tissue specific configuration of enzymes, which can be targeted using proteomics studies since significant differences in enzymes in chronic liver diseases can be profiled. 48,49 Thus, the so called one-carbon metabolism comprises a series of metabolic pathways, providing 1C units (methyl groups) and is crucial for biological methylation reactions. 50 Our study suggests that the monitoring of the one-carbon metabolism in the liver can be a useful strategy to develop a precision medicine for patients with various liver diseases addressing their individual clinical intervention.…”
Section: Analysis Of Dna Methylation and Gene Expression Implicated Thementioning
confidence: 99%
“…Through a variety of mechanisms based on the gut–liver axis, gut microorganisms affect the physiopathological functions of the liver. Exosomes are crucial intercellular communication vehicles 28 . The most widely used preclinical assessment method for liver fibrosis is still animal testing 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Exosomes are crucial intercellular communication vehicles. 28 The most widely used preclinical assessment method for liver fibrosis is still animal testing. 29 Animal models and clinical trials have shown that fibrosis is reversible.…”
Section: Clusters Of Researchmentioning
confidence: 99%
“…Given the intracellular, extracellular, and proinflammatory effects of Gzms on RA, Gzms and their physiological inhibitors may be potential therapeutic targets for RA treatment. It is worth noting that extracellular vesicles (EVs), as one of the important communication carriers between cells and host, may also be a potential contact media between the Gzms family and RA ( 152 ). EVs containing granzyme from NK cells and CTLs require Ca2+-dependent signals to release ( 153 ).…”
Section: Perspectives and Challengesmentioning
confidence: 99%